Determination of Aspergillus pathogens in agricultural products by a specific nanobody-polyclonal antibody sandwich ELISA - Ting Wang (Nature Portfolio, 2017)
Abstract Aspergillus and its poisonous mycotoxins are distributed worldwide throughout the environment and are of particular interest in agriculture and food safety. In order to develop a specific method for rapid detection of Aspergillus flavus to forecast diseases and control aflatoxins, a nanobody, PO8-VHH, highly reactive to A. flavus was isolated from an immunized alpaca nanobody library by phage display. The nanobody was verified to bind to the components of extracellular and intracellular antigen from both A. flavus and A. parasiticus. To construct a sandwich format immunoassay, polyclonal antibodies against Aspergillus were raised with rabbits. Finally, a highly selective nanobody-polyclonal antibody sandwich enzyme-linked immunosorbent assay was optimized and developed. The results revealed that the detection limits of the two fungi were as low as 1 μg mL−1, and that it is able to detect fungal concentrations below to 2 μg mg−1 of peanut and maize grains in both artificially and naturally contaminated samples. Therefore, we here provided a rapid and simple method for monitoring Aspergillus spp. contamination in agricultural products.